Presence of a meningioma in a cervical myelomeningocele sac - Kaplan, Metin; Cobanoglu, Bengu; Kilinc, Ahmet; Yildirim, Hanefi; Taskin, Yakup (Springer Wien, 2008)
An 11-year-old female, presented with a cervical myelomeningocele. Interestingly, the myelomeningocele sac was seen to contain a meningioma. There are no aetiological factors in the embryogenetic period that would lead to such a combination of lesions. In our opinion, the meningioma appeared in a later period because of local factors.
Keywords: Meningioma; Myelomeningocele; Spinal dysraphism; Spinal tumour